2011
DOI: 10.1016/j.neuroimage.2011.06.087
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing risk: Separable encoding of variance and skewness in the brain

Abstract: Risky choice entails a need to appraise all possible outcomes and integrate this information with individual risk preference. Risk is frequently quantified solely by statistical variance of outcomes, but here we provide evidence that individuals’ choice behaviour is sensitive to both dispersion (variance) and asymmetry (skewness) of outcomes. Using a novel behavioural paradigm in humans, we independently manipulated these ‘summary statistics’ while scanning subjects with fMRI. We show that a behavioural sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
78
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 85 publications
16
78
0
2
Order By: Relevance
“…Previous neuroimaging studies found that the AG is activated during decision-making (Ernst et al, 2004;Labudda et al, 2008;Vickery and Jiang, 2009) and moreover, showed that hemodynamic responses in this area during the choice process reflect the probability Berns et al, 2008;Studer et al, 2012) and variance (Symmonds et al, 2011) of potential outcomes. The AG is also thought to be a key area for visuospatial attention.…”
Section: Introductionmentioning
confidence: 94%
“…Previous neuroimaging studies found that the AG is activated during decision-making (Ernst et al, 2004;Labudda et al, 2008;Vickery and Jiang, 2009) and moreover, showed that hemodynamic responses in this area during the choice process reflect the probability Berns et al, 2008;Studer et al, 2012) and variance (Symmonds et al, 2011) of potential outcomes. The AG is also thought to be a key area for visuospatial attention.…”
Section: Introductionmentioning
confidence: 94%
“…A large network of regions that are sensitive to risk has been identified, including the insula, frontal cortices, striatum, cingulate cortex, thalamus, and parietal lobes (1)(2)(3)(4)(5)(6)(15)(16)(17)(18). However, these studies have left a related question largely unaddressed: When confronted with a decision with a given amount of risk, what key differences in neural activity predict whether the subject will go on to make the risky or safe choice?…”
mentioning
confidence: 99%
“…Furthermore, the results are supported by medical studies showing that variance and skewness are processed by two different brain areas, both of which are known targets of cortisol (Symmonds et al 2011). …”
supporting
confidence: 52%